2020
DOI: 10.1093/nar/gkaa790
|View full text |Cite
|
Sign up to set email alerts
|

RMDisease: a database of genetic variants that affect RNA modifications, with implications for epitranscriptome pathogenesis

Abstract: Deciphering the biological impacts of millions of single nucleotide variants remains a major challenge. Recent studies suggest that RNA modifications play versatile roles in essential biological mechanisms, and are closely related to the progression of various diseases including multiple cancers. To comprehensively unveil the association between disease-associated variants and their epitranscriptome disturbance, we built RMDisease, a database of genetic variants that can affect RNA modifications. By integratin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 103 publications
1
50
0
Order By: Relevance
“…There have been several reports that gene mutations usually cause phenotypic changes, which are in turn closely related to carcinogenesis and aging (Gonzalo et al, 2017;Kaur et al, 2018;Chen et al, 2021). Concurrently, a meta-analysis of studies on copy number amplification has shown that copy number changes affect genes involved in cell cycle regulation, retinoic acid signaling, complement system, and antigen presentation, which may cause cancer (Brown et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been several reports that gene mutations usually cause phenotypic changes, which are in turn closely related to carcinogenesis and aging (Gonzalo et al, 2017;Kaur et al, 2018;Chen et al, 2021). Concurrently, a meta-analysis of studies on copy number amplification has shown that copy number changes affect genes involved in cell cycle regulation, retinoic acid signaling, complement system, and antigen presentation, which may cause cancer (Brown et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggested that gene alterations may affect RNA modifications and disease associations (Song et al, 2020;Chen et al, 2021). Here, we analyzed the alterations in NSUN2 and NSUN6 from the cBioportal database, with these alterations mainly including mutations, deletions, copy number gains, and amplifications.…”
Section: Gene Alterations and Signaling Pathways Of Prognosis-relatedmentioning
confidence: 99%
“…Similar to m6AVar, m 6 A-Atlas also annotated the potential involvement of m 6 A sites in pathogenesis by integrating GWAS information. Similar to RMVar, RMDisease [131] collected eight types of RNA modifications and their disease-associated variants. Importantly, RMDisease integrated multiple algorithms and used more information and provides quantitatively the impact of the genetic variants on RNA modification.…”
Section: Functional Annotation Of Rna Methylation Sitesmentioning
confidence: 99%
“…Furthermore, comprehensive information on reliable m6A methylation sites and peaks from MeRIP-seq data are summarized in m6A-Atlas ( Tang et al, 2020 ) and REPIC ( Liu et al, 2020b ), respectively. Bioinformatics resources such as RMDisease ( Chen K. et al, 2020 ) and RMVar ( Luo et al, 2020 ) can aid in better understanding the association between various epitranscriptomic modifications and their probable disease relevance.…”
Section: M6a Rna Modification and Associated Regulatorsmentioning
confidence: 99%